Strategy for Strengthening Aswaja An-Nahdliyah Values through the Istigotsah Religious Activities Program at Manbail Huda Jenu High School in the 2024/2025 Academic Year - Syafa Layyina Amalia (Al-Ard: Journal of Education, 2025)
This study discusses strategies for strengthening the values of Ahlussunnah wal Jama’ah (Aswaja) An-Nahdliyah through the Istighosah religious activity program at SMA Manba’il Huda Jenu in the 2024/2025 academic year. The background of this research is based on the increasing challenges of radicalism and extreme religious understanding among the younger generation, which requires systematic efforts to instill moderate, tolerant Islamic values rooted in Aswaja principles. This study employs a qualitative method with a descriptive approach using observation, interviews, and documentation techniques. The findings reveal that the Istighosah program plays a significant role in strengthening Aswaja An-Nahdliyah values, including tawassuth (moderation), tasamuh (tolerance), tawazun (balance), and i’tidal (justice). Through the habituation of religious activities, students not only enhance their spirituality but also develop strong religious character, nationalism, and resilience against radical ideologies. Therefore, the Istighosah program is an effective strategy for internalizing Aswaja An-Nahdliyah values within the educational environment.